"I used to be an addict. I'm still an addict. I'm always going to be a recovering addict": Understanding the challenges of individuals seeking recovery. (4th March 2019) - Parker, Kimberly A.; Ivanov, Bobi; Thieneman, Allison; Wombacher, Kevin; Watterson, Tara; Burchett, Molly; Adams, Elizabeth
ABSTRACT: Background and Objective: Although preventable, substance addiction has become one of the most prominent public health problems facing the nation. As a result, treatment programs and centers have focused resources and efforts on aiding individuals on their path to long-term recovery. However, the constant threat, reinforced by high incidence, of relapse presents a major obstacle to long-term recovery. Relapse prevention programs are designed to target social and psychological factors contributing to lapses in sobriety. Yet, the exact factors that can impact long-term recovery and prevent or lower the instances of relapse are not always clear. The current study explores the major contributors to relapse as experienced in a male residential treatment center. Methods: The data were gathered through 31 in-depth interviews in a residential halfway house treatment facility for substance use recovery. Results: The results of the study underscored social support and interpersonal relationships as major factors impacting long-term recovery. More specifically, lack of efficacy in managing interpersonal relationships and building new support networks were identified as essential barriers to long-term recovery. Conclusions: The management of interpersonal relationships seems to be a key to long-term recovery, which emphasizes the need for strategies that underscore the development of positive relationships that will strengthen resistance to relapse and long-term recovery.